Evaluation of the Accuracy of the Delta Life DL 1000 Oscillometric Monitor for Blood Pressure Measurement in Anesthetized Dogs of Different Weight Ranges - Silva Correia, Bárbara; Raposo Monteiro, Eduardo; Barbieri Ferronatto, João Victor; Branquinho Queiroga, Luciana; Herrera Becerra, José Ricardo (Acta Scientiae Veterinariae, 2020)
Background: Arterial blood pressure is one of the most commonly variables monitored during anesthetic procedures in veterinary patients. The most reliable method for measuring arterial blood pressure in dogs and cats is the direct (invasive) method. However, the oscillometric method is less complex and more practical for clinical routine in small animals. Nevertheless, oscillometric monitors present great variability in accuracy. The present study aimed to determine the accuracy of the Delta Life DL 1000 oscillometric monitor for measurement of systolic, mean and diastolic blood pressures (SAP, MAP and DAP, respectively) in anesthetized dogs of different weight ranges. Materials, Methods & Results: This study was approved by the Institutional Ethics Committee of Animal Use. Fifteen female dogs of different breeds, weighing 11.6 ± 10.0 kg and with a mean age of 48 ± 51 months were used. All animals were scheduled for elective surgery under general anesthesia in the Institution Veterinary Hospital. Dogs were anesthetized with morphine, propofol and isoflurane and had one 20 or 22 gauge catheter introduced into the dorsal pedal artery for continuous, invasive monitoring of SAP, MAP and DAP. A blood pressure cuff was positioned over the middle third of the radius and connected to Delta Life DL 1000 monitor. Oscillometric readings of SAP, MAP and DAP were registered every 5 minutes, and invasive values were simultaneously recorded. Values obtained with both methods were compared (invasive versus oscillometric) by use of the Bland Altman method to determine the bias, standard deviation of bias and 95% limits of agreement. The percentages of errors between the methods within 10 mmHg and within 20 mmHg were calculated. The results obtained were compared with the criteria from the American College of Veterinary Internal Medicine (ACVIM) for validation of indirect methods of arterial blood pressure measurement. Data were stratified into two groups according to the weight: < 10 kg (Group 1; n = 9); and ≥ 10 kg (Group 2; n = 6). In Group 1, 119 paired measurements were obtained, four of which classified as hypotension (SAP < 90 mmHg), 98 as normotension (SAP from 90 to 140mmHg) and 17 as hypertension (SAP > 140 mmHg). Bias (± SD) values in Group 1 were as follows: SAP, 5.2 ± 18.1 mmHg; MAP, -3.4 ± 17.2 mmHg; and DAP, 12.0 ± 17.5 mmHg. The percentages of errors within 10 mmHg were 40.3% for SAP; 45.4% for MAP and 28.6% for DAP. The percentages of errors within 20 mmHg were 72.3% for SAP, 84.0% for MAP and 68.1% for DAP. In Group 2, 66 paired measurements were obtained, nine of which classified as hypotension, 56 as normotension and one as hypertension. Bias (± SD) in Group 2 were as follows: SAP, 13.6 ± 14.3 mmHg; MAP, -1.1 ± 13.5 mmHg; and DAP, 8.2 ± 16.0 mmHg. The percentages of errors within 10 mmHg were 33.3% for SAP, 77.3% for MAP and 33.3% for DAP. The percentages of errors within 20 mmHg were 65.1% for SAP, 92.4% for MAP and 83.4% for DAP. Discussion: Based on the results of this study and reference criteria from the ACVIM, the Delta Life DL 1000 monitor had a poor accuracy for SAP, MAP and DAP and did not meet the criteria from the ACVIM in anesthetized dogs under 10 kg. Measurements of MAP in dogs ≥ 10 kg met the ACVIM criteria, but measurements of SAP and DAP did not. Based on the findings in this study, the DL 1000 oscillometric monitor is not recommended for blood pressure measurement in anesthetized dogs < 10 kg. In dogs ≥ 10 kg, measurements of MAP yielded acceptable values, but SAP and DAP measurements did not.